2016
DOI: 10.1002/2015jd024274
|View full text |Cite
|
Sign up to set email alerts
|

Peak precipitation intensity in relation to atmospheric conditions and large‐scale forcing at midlatitudes

Abstract: Research on relations between atmospheric conditions and extreme precipitation is important to understand and model present-day climate extremes and assess how precipitation extremes might evolve in a future climate. Here we present a statistical analysis of the relation between large-scale conditions and hourly precipitation at midlatitudes, by using observations of the Netherlands combined with a regional reanalysis. The aim is to gain a better understanding of the typical large-scale atmospheric conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…However, further research is needed to test this assumption in our study region. Recent contributions to the literature by Loriaux et al (2016a) and Loriaux et al (2016b) demonstrate that considering relative humidity alone is not sufficient to explain the intensification of extreme precipitation. Through including atmospheric control factors such as large scale moisture convergence and atmospheric stability, they deliver valuable contributions to process understanding.…”
Section: How Regional Scaling Factors Relate To Absolute Rainfall Intmentioning
confidence: 99%
“…However, further research is needed to test this assumption in our study region. Recent contributions to the literature by Loriaux et al (2016a) and Loriaux et al (2016b) demonstrate that considering relative humidity alone is not sufficient to explain the intensification of extreme precipitation. Through including atmospheric control factors such as large scale moisture convergence and atmospheric stability, they deliver valuable contributions to process understanding.…”
Section: How Regional Scaling Factors Relate To Absolute Rainfall Intmentioning
confidence: 99%
“…Several studies have suggested that the changes in upward motion and moisture are directly related to extreme rainfall changes (Loriaux et al, ; O'Gorman & Schneider, ). To better understand the moisture processes with the occurrence of the extreme rainfall, we have examined the moisture flux divergence ( 1g()qV), which is considered as an important factor of heavy rainfall during BSISO1 phases and BSISO2 phases.…”
Section: The Influences Of Bsiso On Extreme Rainfallmentioning
confidence: 99%
“…In order to further demonstrate the contributions of upward motion and vertical moisture transport to rainfall extremes, Figures and show the mean profiles of vertical pressure velocity ( ω ) and vertical moisture advection ( ωqp), which are supposed to be related to extreme rainfall (Loriaux et al, ). Figure shows the vertical velocity profiles, which are closely related to large‐scale convergence.…”
Section: The Influences Of Bsiso On Extreme Rainfallmentioning
confidence: 99%
“…Several studies have suggested that changes in extremes are directly linked to changes in upward motion and moisture, among other factors [28,29,53,54]. To better understand the moisture processes associated with the occurrence of the extreme rainfall, we have examined column-integrated horizontal moisture convergence (− Figure 5a-c, but with the shadings representing column-integrated moisture advection and the vectors representing 850-hPa winds.…”
Section: Physical Basis Of Extreme Rainfall Changesmentioning
confidence: 99%
“…Unlike moisture convergence, the direct contributions from horizontal moisture advection may be insignificant (Figure 5d-f). Figure 6 shows the mean profiles of vertical pressure velocity ( ω , as seen in Figure 6a) and vertical moisture advection ( p ∂ ∂q -ω , as seen in Figure 6b), which are supposed to be related to the extreme rainfall [54]. Figure 6a shows the vertical velocity profile, which is an indirect measure of the large-scale convergence.…”
Section: Physical Basis Of Extreme Rainfall Changesmentioning
confidence: 99%